HUBUNGAN PERSEPSI PEMAKAIAN ALAT KONTRASEPSI DENGAN KEJADIAN UNMET NEED PADA PASANGAN USIA SUBUR - Ni Wayan Ariadi Putri; Kadek Widiantari (JOMIS (Journal of Midwifery Science), 2022)
The high incidence of unmet need for family planning is where there are various perceptions about contraceptives that become the basis for a person to be afraid to use contraceptives and this can also make the number of unmet need high. The design of this study was analytic observational with a cross-sectional approach. The population in this study were all couples of childbearing age in the Denpasar City area for the period of 2020 and the number of samples in this study amounted to 96 couples of childbearing age using the proportional stratified random sampling technique. Data was collected by distributing online questionnaires and the data analysis technique used was the Chi-Square test. The purpose of this study was to determine the relationship between perceptions of contraceptive use and the incidence of unmet need for family planning in couples of childbearing age. The results of this study found that there was a relationship between perceptions of contraceptive use (p=0.477) and the incidence of unmet need for family planning in couples of childbearing age. The results of this study are expected to be a reference to help increase the coverage of contraceptive use in the Denpasar City area.